درجة تطبيق معايير الجودة (السياق المؤسسي) في مؤسسات التعليم العالي الأردنية والسعودية: دراسة مقارنة - النصير، يوسف محمد; الرواشدة، ناجى محمد عواد; القيسي، حسين عبدالنبي (جامعة أسيوط - مركز تطوير التعليم الجامعي, 2016)
The aim of the study is to identify the degree of applying the Quality Standards (institutional context standards) in the institutions of higher education in Jordan and Saudi Arabia. To achieve the objectives of the study a descriptive approach has been applied, where a stratified random sampling has been chosen, the sample consists of 119 members from administrative leaders in the public universities of Jordan and Saudi Arabia. The tool of the study is a questionnaire, which has been developed by the researchers after proving its psychometric characteristics (reliability and validity). The questionnaire consists of 32 items covering two domains; the first domain is about the vision, the mission and the goals (strategic planning) and it consists of 12 items. The second domain is about authorities and administration (governance) and it consists of 20 items. The data was analyzed; the results showed that there was a medium degree of commitment in applying the institutional context standards in the universities of Jordan and Saudi Arabia where its mean reaches (13.3) in the two fields of the tool related to the domains: strategic planning and governance. Also, results showed that there were no statistically significant differences in the degree of administrative leaders' commitment to apply the institutional context standards due to the study variables (university, experience, scientific qualification and the interaction between them). Researchers recommend that administrative leaders should get a very good training in the universities of Jordan and Saudi Arabia by attending training courses and workshops to equip them with the competences and skills their jobs need.
هدفت هذه الدراسة إلى التعرف على درجة تطبيق معايير الجودة (السياق المؤسسي) في مؤسسات التعليم العالي الأردنية والسعودية، ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي بصورته المسحية حيث تم اختيار عينة طبقية عشوائية قوامها 119 فرداً من القادة الإداريين في الجامعات الحكومية الأردنية والسعودية، حيث وزعت عليهم أداة الدراسة وهي استبانة تم تطويرها من قبل الباحثون مكونة من 32 فقرة، تضمنت محورين: المجال الأول حول الرؤية والرسالة والأهداف (التخطيط الاستراتيجي) مكونا من 12 فقرة والمجال الثاني حول السلطات والإدارة (الحوكمة) مكونا من 20 فقرة. وتم التأكد من خصائصها السيكومترية (الصدق والثبات). وبعد تحليل البيانات التي تم جمعها تبين وجود درجة التزام متوسطة في تطبيق معايير السياق المؤسسي في الجامعات الأردنية والسعودية حيث بلغ متوسطها الحسابي (3.12) وفي مجالي الإدارة المتعلقين بمعيار التخطيط الاستراتيجي والحوكمة. كما بينت النتائج عدم وجود فروق ذات دلالة إحصائية في درجة التزام القادة الإدارييين بتطبيق معايير السياق المؤسسي تعزي إلى متغيرات الدراسة (الجامعة، والخبرة، والمؤهل العلمي والتفاعل بينهم). وقد أوصى الباحثون بضرورة إعداد القادة الإداريين بالجامعات الأردنية والسعودية إعداداً جيداً وذلك من خلال الدورات والورش التدريبية لتزويدهم بالكفايات والمهارات التي يحتاجها عملهم.
Keywords: المعايير العالمية -- الأداء المؤسسى -- المؤسسات التعليمية -- التعليم الجامعى -- الأردن -- السعودية